Evaluation of the Red Hook Community Justice Center in Brooklyn, (New York City, New York), 1998-2010 - Lee, Cynthia G. ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.The study examined four research questions: (1) Was the Red Hook Community Justice Center (RHCJC) implemented according to plan?; (2) Did RHCJC make a difference in sanctioning, recidivism, and arrests?; (3) How did RHCJC produce any observed reductions to recidivism and arrests?; and (4) Is RHCJC cost-efficient from the viewpoint of taxpayers? The community survey (Red Hook Resident Data, n = 95) was administered by research teams in the spring and summer of 2010. Teams generally went house-to-house ringing apartment buzzers at varying times of day, usually on the weekend when working people are more likely to be home or approached people on the sitting on park benches to conduct interviews.In autumn 2010, the research team administered a survey to 200 misdemeanor offenders (Red Hook Offender Data, n = 205) who were recruited from within the catchment area of the Red Hook Community Justice Center (RHCJC) using Respondent Driven Sampling (RDS).To examine how the RHCJC was implemented (Red Hook Process Evaluation Data, n= 35,465 and Red Hook Work File Data, n= 3,127), the research team relied on a diverse range of data sources, including 52 structured group and individual interviews with court staff and stakeholders carried out over five site visits; observation of courtroom activities and staff meetings; extensive document review; and analysis of case-level data including all adult criminal cases and some juvenile delinquency cases processed at the Justice Center from 2000 through 2009. To aid in understanding the RHCJC's impact on the overall level of crime in the catchment area, researchers obtained monthly counts (Arrest Data, n = 144) of felony and misdemeanor arrests in each of the three catchment area police precincts (the 72nd, 76th, and 78th precincts).